2017
DOI: 10.1123/jab.2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Optimal Pole Length for Double Poling in Cross Country Skiing?

Abstract: 15The aim of this study was to determine the effects of pole length on energy cost and 16 kinematics in cross country double poling. Seven sub-elite male athletes were tested using pole 17 sets of different lengths (ranging between 77 and 98% of participants' body height). Tests were 18 conducted on a treadmill, set to a 2% incline and an approximate racing speed. Poling forces,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 16 publications
5
27
0
Order By: Relevance
“…Our findings in this particular study are in line with earlier investigations that claimed that longer poles in classic DP of up to ~ 90% of body height reduced the VO 2 -cost [11, 12, 14]. In the present study, the skiers were tested in the G3 ski skating sub-technique, and since it is assumed that performance in DP and G3 are limited by the same physiological and biomechanical factors with respect to at least upper-body work [9, 10], it is reasonable to assume that LP in G3 have the same advantages.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings in this particular study are in line with earlier investigations that claimed that longer poles in classic DP of up to ~ 90% of body height reduced the VO 2 -cost [11, 12, 14]. In the present study, the skiers were tested in the G3 ski skating sub-technique, and since it is assumed that performance in DP and G3 are limited by the same physiological and biomechanical factors with respect to at least upper-body work [9, 10], it is reasonable to assume that LP in G3 have the same advantages.…”
Section: Discussionsupporting
confidence: 93%
“…Previous research has shown the beneficial effects of using longer poles (self-selected + 5–10 cm) in DP [7, 11, 12, 13, 14]. During DP, the force is transferred to the ground via the poles, and pole length seems to have a crucial influence on VO 2 -cost and performance during DP in classic skiing [11].…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated the relationship between pole length and O 2 -cost, showing that longer poles induced a lower O 2 -cost compared with shorter and self-selected pole lengths. These results are in accordance with Losnegard et al ( 2017 ) and Onasch et al ( 2016 ), and imply that a pole length up to at least ~ 90% of body height reduces the O 2 -cost during DP on a treadmill. Notably, these studies have exclusively tested male skiers, and the influence of pole length on O 2 -cost during DP for female skiers is currently not known.…”
Section: Discussionsupporting
confidence: 91%
“…During DP, propulsive forces are transferred sorely through the poles, suggesting that pole length is an important parameter for O 2 -cost and performance (Losnegard et al 2017 ). However, previous studies have exclusively investigated the influence of pole length in flat or slightly inclined terrain, i.e., < 2.5° (Hansen and Losnegard 2010 ; Hoffman et al 1994 ; Losnegard et al 2017 ; Nilsson et al 2003 , Onasch et al 2016 ) and little is known about how pole length influences performance or performance-related mechanisms on steeper inclines.…”
Section: Introductionmentioning
confidence: 99%
“…Typical modern racing poles can transmit forces as high as 500–800 N ( Swarén et al, 2013b ), a value much higher than that normally applied during poling, but which faster skiers can produce at maximal speed ( Stöggl and Holmberg, 2011 ). A major change here involved lengthening classical skiing poles ( Nilsson et al, 2003 ; Hansen and Losnegard, 2010 ; Stöggl and Karlöf, 2013 ; Losnegard et al, 2017 ), which improved oxygen cost ( Losnegard et al, 2017 ; Onasch et al, 2017 ) and poling mechanics and enhanced peak velocities on both flat and uphill terrain ( Stöggl et al, 2010a ). However, pole length is limited by recent FIS regulations (see further below).…”
Section: Evolution Of Equipmentmentioning
confidence: 99%